Biopsychosocial function analyses changes the assessment of the ability to work in patients on long-term sick-leave due to chronic musculoskeletal pain: The role of undiagnosed mental health comorbidity. Issue 3 (May 2013) - Olaya-Contreras, Patricia; Styf, Jorma
Aims : To study the prevalence of somatic and mental health comorbidity and the use of opioid medication among patients on long-term sick-leave due to chronic musculoskeletal pain (CMP); to compare an orthopaedic-based assessment of ability to work with a team assessment; to investigate the relationship between intensity of pain and psychosocial characteristics in this group. Methods : A cross-sectional study was carried out with 174 consecutive patients on sick-leave for a mean of 21 months. All were referred from the Social Insurance Office for orthopaedic evaluation and assessment of the ability to work. Of them, only 83/174 patients were referred by the Office for psychiatric evaluation. Results : Neck pain was the main cause of disability. Patients with neck pain often suffered pain in more than two sites, and greater intensity of pain. Thirty-four percent of all participants had been prescribed opioid medication before consultation. Degrees of disability, unemployment, low degree of education and to be an immigrant were related to intensity of pain. Unrecognized psychiatric disorders changed the main cause of inability to work in 69% of patients who underwent both orthopaedic and psychiatric evaluation. Conclusions : An evaluation based on biopsychosocial function is valuable in reaching an accurate assessment of the patient's diagnosis, and ability to work in CMP. Ability to work and degree of sick-leave in patients on long-term sick-leave is determined to a large extent by undiagnosed mental health comorbidities, and not solely somatic complaints.